Potential of the Agricultural Sector Based on Classification and Its Role in Sustainable Development in OKU Regency - Nurjanah, Nurjanah; Munajat; Oktarina, Yetty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The agricultural sector is essential for national development, especially in managing and using key resources, emphasizing food commodities. This sector is essential for economic growth, as a significant portion of the Indonesian population depends on agriculture for sustenance. This study analyzes data from three primary sectors: agriculture, forestry, and plantations, explicitly concentrating on OKU Regency in South Sumatra Province. The assessment utilizes Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology methodologies to analyze the viability and sustainability of specific sectors.The findings indicate that the agriculture, forestry, and fisheries sectors are fundamental and prospective contributors to the Gross Regional Domestic Product (GRDP) in OKU Regency, with a Location Quotient (LQ) value of 2.41, signifying these industries sufficiently satisfy local demand from 2014 to 2023. A comparison of LQ (2.41) and DLQ (2.81) further substantiates that these sectors are predominant and will persist as fundamental sectors in the future, indicating their sustainability. Furthermore, the Klassen Typology analysis reveals that OKU Regency exhibits a growth pattern in which the regional growth rate (r_ik) surpasses the overall sector growth rate (r_i). However, the contribution to GRDP (Y_ik) remains below the average (Y_i). This study emphasizes the agriculture, forestry, and fisheries sectors as pivotal catalysts for regional development and significant contributions to the Sustainable Development Goals (SDGs), especially in promoting sustainable economic growth, environmental conservation, and food security. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land